Lime sand polymeric material and preparation method thereof

Through the use of flour ash, desert sand/ocean sand, slag, alkaline stimulus, solvents and solvent preparation materials in the desert area or in the ocean and island environment, it solves the problem of high and low strength in the existing technology in the existing technology The effect of high strength, low cost and waste resource use.

CN119330643APending Publication Date: 2025-01-21LIAONING HAITIANGE ENVIRONMENTAL PROTECTION TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411265027.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, the building materials used in desert areas or marine or island environments have high cost and low strength, making it difficult to meet the construction needs in special environments.

Method used

Gray sand polymeric material is used. Its formula includes fly ash, desert sand/ocean sand, slag, alkali activator and solvent. Through specific weight ratio and grinding activation steps, a high-strength gray sand polymeric material is formed.

Benefits of technology

The gray sand aggregation materials with high strength, easy raw materials, and low cost are suitable for the field of desert buildings and sea industry materials. It can effectively reduce building costs and deal with solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330643A_ABST
    Figure CN119330643A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly functional new materials, and relates to a lime sand polymeric material and a preparation method thereof, the lime sand polymeric material comprises the following raw materials by weight: 100-400 parts of fly ash, 100-1000 parts of desert sand / ocean sand, and 50-300 parts of slag; 30-220 parts of an alkali activator and 25-200 parts of a solvent; wherein the weight ratio of the fly ash to the desert sand is 0.2-1.4. Through interaction of the fly ash and the desert sand in a specific weight ratio, the ash-sand polymeric material obtained in the invention has better mechanical properties, uses more desert sand and fly ash, does not need to add other various aggregates, fibers and other components, and is simpler in components and convenient to manufacture; the desert sand is a raw material which is low in cost and easy to obtain in desert, and the fly ash and the slag are solid wastes needing harmless treatment, so that the ash sand polymeric material is relatively low in manufacturing cost, the solid wastes can be effectively treated, and resource utilization of the wastes is realized on the basis of reducing the polymer cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new environmentally friendly functional materials and relates to a gray sand polymer material and a preparation method thereof. Background Art

[0002] Geopolymer materials are also known as geopolymer cement. Geopolymer materials are generally obtained by mixing kaolin, alkaline activator solution and siliceous and aluminous materials. Fly ash, as a raw material containing silicon and aluminum elements required for geopolymerization, has gradually been used as one of the raw materials for geopolymer materials in recent years. At the same time, fiber materials are often added in the existing technology to increase the performance of geopolymer materials, and aggregates of different coarseness and fineness are mixed with the geopolymerization raw materials. The aggregates used often include river sand, machine-made sand, stones, etc.

[0003] In some cases, such as in desert areas or in ocean and island environments, since the cost of obtaining conventional building materials such as river sand, machine-made sand, and stones is relatively high, in order to reduce construction costs, it is necessary to obtain building materials as locally as possible. For example, in desert areas, desert sand is relatively easy to obtain, and increasing the content of desert sand in geopolymer materials will reduce the manufacturing cost of geopolymer materials. Although the prior art discloses the use of desert sand in the preparation of geopolymer building materials, the desert sand content is relatively small, and a large amount of machine-made sand is still consumed, and other aggregates need to be added. The raw material composition is relatively complex, resulting in a relatively high cost of oligomeric materials, and the actual application will face the problem of low strength.

[0004] Based on this, the present invention aims to seek a geopolymer material with good strength, readily available raw materials and low cost, so as to better apply it in the field of building materials for special environments. Summary of the invention

[0005] In order to solve one of the above technical problems, the present invention provides a gray sand polymer material and a preparation method thereof.

[0006] According to a first aspect of the present invention, the present invention provides a ash-sand polymer material, which includes the following raw materials in parts by weight: 100-400 parts of fly ash, 100-1000 parts of desert sand / ocean sand, 50-300 parts of slag; 30-220 parts of alkali activator, 25-200 parts of solvent; wherein the weight ratio of the fly ash to the desert sand is 0.2-1.4.

[0007] Specifically, in parts by weight, in some embodiments of the present application, the amount of fly ash can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts, 260 parts, 270 parts, 280 parts, 290 parts, 300 parts, 310 parts, 320 parts, 330 parts, 340 parts, 350 parts, 360 parts, 370 parts, 380 parts, 390 parts, 400 parts, or a range consisting of any two of the above values.

[0008] Specifically, in parts by weight, in some embodiments of the present application, the amount of the desert sand / ocean sand can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 142 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts, 260 parts, 270 parts, 280 parts, 290 parts, 300 parts, 310 parts, 320 parts, 330 parts, 340 parts, 350 parts, 360 parts, 370 parts, 380 parts, 390 parts, 400 parts, 410 parts, 420 parts, 430 parts, 440 parts, 450 parts, 460 parts, 470 parts, 480 parts, 490 parts, 500 parts, 510 parts, 520 parts, 530 parts 30, 540, 550, 560, 570, 573, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 7 80, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000, or a range consisting of any two of the above values.

[0009] Specifically, in some embodiments of the present application, the amount of slag can be 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts, 260 parts, 270 parts, 280 parts, 290 parts, 300 parts or a range consisting of any two of the above values.

[0010] Specifically, in some embodiments of the present application, the amount of the base activator can be 30 parts, 40 parts, 50 parts, 60 parts, 64 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 115 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, 210 parts, 220 parts, or 10 parts of the above.

[0011] Specifically, in parts by weight, in some embodiments of the present application, the amount of the solvent can be 25 parts, 30 parts, 32 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 87 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 120 parts, 130 parts, 135 parts, 140 parts, 150 parts, 160 parts, 165 parts, 170 parts, 180 parts, 190 parts, 200 parts, parts, 90 parts, 95 parts, 100 parts or a range consisting of any two of the above values.

[0012] Specifically, in parts by weight, the weight ratio of the fly ash to the desert sand can be 0.2, 0.25, 0.3, 0.35, 0.40, 0.45, 0.50, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4 or a range consisting of any two of the above values. In some embodiments of the present application, the ratio of the fly ash to the desert sand is 0.46-0.9; in some embodiments of the present application, the ratio of the fly ash to the desert sand is 0.47-0.8; more preferably, the ratio of the fly ash to the desert sand is 0.7.

[0013] In some embodiments of the present application, the solvent includes one or more of pure water, tap water, brackish water, seawater, and waste alkali liquid.

[0014] In some embodiments of the present application, the alkaline activator is selected from two or more of sodium silicate, sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0015] In some embodiments of the present application, the alkaline activator is selected from a combination of sodium silicate and at least one of sodium hydroxide, potassium hydroxide, and calcium hydroxide. The present invention has found in exploration that the performance of the obtained gray sand polymer material is better when sodium silicate is combined with at least one of sodium hydroxide, potassium hydroxide, and calcium hydroxide as an alkaline activator.

[0016] In some embodiments of the present application, the alkali activator includes 25-170 parts of sodium silicate and 5-50 parts of sodium hydroxide in parts by weight. Specifically, the amount of sodium silicate in the alkali activator can be 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 32 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 87 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 120 parts, 130 parts, 135 parts, 140 parts, 150 parts, 155 parts, 160 parts, 170 parts, 180 parts, 185 parts, 190 parts, 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts, 260 parts, 270 parts, 280 parts, 290 parts, 300 parts, 310 parts, 320 parts, 350 parts, 360 parts, 370 parts, 380 parts, 390 parts, 400 parts, 410 parts, 420 parts, 430 parts, 440 parts, 450 parts, 460 parts, 470 parts, 480 parts, 490 parts, 500 parts, 510 parts, 510 parts, 520 parts, 530 parts, 530 parts, 540 parts, 550 parts, 0 parts, 150 parts, 160 parts, 165 parts, 170 parts, 180 parts, 190 parts, 200 parts, parts, 90 parts, 95 parts, 100 parts, 105, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, 150 parts, 155 parts, 160 parts, 165 parts, 170 parts, or a range consisting of any two of the above values. Specifically, the amount of sodium hydroxide in the alkaline activator can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts or a range consisting of any two of the above values. The present invention has been found in exploration that the performance of the gray sand polymer material obtained by combining sodium silicate and sodium hydroxide in a specific ratio as an alkaline activator is better.

[0017] In some embodiments of the present application, the alkali activator includes 30-150 parts of sodium silicate and 10-35 parts of sodium hydroxide, by weight.

[0018] In some embodiments of the present application, in parts by weight, the amount of fly ash used is 350 parts, the amount of desert sand used is 500 parts, the amount of alkali activator used is 192.3 parts, and the amount of slag used is 150 parts.

[0019] In some embodiments of the present application, the desert sand particle size is aeolian sand of 100 to 400 mesh, and the particle size distribution of the desert sand is between 0.074 and 0.250 mm; specifically, the desert sand particle size can be 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, or a range consisting of any two of the above values. Specifically, the particle size distribution of the desert sand can be 0.074 mm, 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.20 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.250 mm, or a range consisting of any two of the above values.

[0020] In some embodiments of the present application, the desert sand comes from the Taklimakan Desert.

[0021] In some embodiments of the present application, the desert sand has an average particle size of 67.47 μm, an average sphericity of 0.76, an average convexity of 0.94, an average aspect ratio of 0.70, and an average roundness of 0.38.

[0022] In some embodiments of the present application, the marine sand is taken from an ocean beach and is screened and processed to remove impurities, and the fineness modulus is 2.1 to 2.6.

[0023] In some embodiments of the present application, the compressive strength of the gray sand polymer material is 71.70 MPa.

[0024] In some embodiments of the present application, the fly ash includes one or more of primary, secondary, and tertiary fly ash; the primary fly ash refers to Class F fly ash that meets the Class I physical and chemical property requirements of GB / T 1596; the secondary fly ash refers to Class F fly ash that meets the Class II physical and chemical property requirements of GB / T 1596; the tertiary fly ash refers to Class F fly ash that meets the Class III physical and chemical property requirements of GB / T1596.

[0025] In some embodiments of the present application, the fly ash contains 3-5% calcium oxide, 49-51% silicon oxide, 26-28% aluminum oxide, and 6-8% iron oxide.

[0026] In some embodiments of the present application, the fly ash is selected from primary fly ash, which is air-selected primary fly ash produced by a coal-fired power generation unit of 600 MW or more and which is not ground and complies with GB / T 1596.

[0027] In some embodiments of the present application, the fly ash is selected from secondary fly ash.

[0028] In some embodiments of the present application, the fly ash is selected from tertiary fly ash.

[0029] According to a second aspect of the present invention, the present invention provides a method for preparing the gray sand polymer material as described in any one of the first aspects of the present invention, comprising the following steps:

[0030] (1) Preparing a ash-sand polymerizer: grinding and activating slag and fly ash to obtain a ash-sand polymerizer;

[0031] (2) preparing a ash sand polymerization liquid: grinding an alkali activator, adding a solvent and mixing well to obtain an ash sand polymerization liquid;

[0032] (3) Preparation of ash-sand polymer material: Mix ash-sand polymerizer and desert sand and / or ocean sand, then add alkali activator and solvent, stir evenly, pour into a mold, vibrate and compact, cure and demould, and obtain ash-sand polymer material.

[0033] In some embodiments of the present application, in step (1), the grinding activation conditions include: a grinding speed of 700-900 r / min, forward and reverse grinding for 20-40 min each, to 700-900 mesh. Preferably, the grinding activation conditions include: a grinding speed of 800 r / min, forward and reverse grinding for 30 min each, to 800 mesh. Specifically, a ball mill is used for grinding.

[0034] In some embodiments of the present application, in step (2), the conditions for alkali-induced grinding include: grinding speed 400-600 r / min, grinding time 10-30 min. Preferably, in step (2), the conditions for alkali-induced grinding include: grinding speed 500 r / min, grinding time 20 min.

[0035] In some embodiments of the present application, in step (2), the amount of the solvent used is 22-100 parts by weight; specifically, in step (2), the amount of the solvent used, by weight, can be: 22 parts, 25 parts, 27 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts or a range consisting of any two of the above values.

[0036] In some embodiments of the present application, in step (2), the amount of the solvent used is 30-70 parts by weight.

[0037] In some embodiments of the present application, in step (3), the amount of the solvent used is 3-100 parts by weight; in step (3), the amount of the solvent used can be: 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 22 parts, 25 parts, 27 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts or a range consisting of any two of the above values.

[0038] In some embodiments of the present application, in step (3), the amount of the solvent used is 3-50 parts by weight.

[0039] In some embodiments of the present application, in step (2), the specific method of grinding the alkaline activator and then adding the solvent water to mix is: first, adding the solvent to sodium hydroxide to dissolve to prepare a sodium hydroxide solution, and then dissolving the ground sodium silicate into the sodium hydroxide solution to obtain a gray sand polymerization liquid.

[0040] In some embodiments of the present application, in step (3), the desert sand used comes from the Taklimakan Desert, has an average particle size of 67.47 μm, an average sphericity of 0.76, an average convexity of 0.94, an average aspect ratio of 0.70, and an average roundness of 0.38;

[0041] In some embodiments of the present application, the pouring in step (3) includes: during the pouring process, the uniformity, density and integrity of the ash-sand-polymer mixture should be effectively controlled. The ash-sand-polymer mixture is loaded into the mold at one time. When loading, a spatula should be used to tamp along the inner wall of the mold, and the ash-sand-polymer mixture should be higher than the upper mouth of the mold. The mold should be attached to or fixed on a vibration table. During vibration, the mold should be prevented from jumping freely on the vibration table. The vibration should continue until the surface slurry comes out and there are no obvious large bubbles overflowing. Over-vibration is not allowed. When pouring larger structures, the pouring should be done in layers. The maximum thickness of each layer should not exceed 350mm, and the upper layer of concrete should be poured before the lower layer of concrete begins to set. After pouring and forming, the pouring surface should be smoothed mechanically or manually before the ash-sand-polymer mixture is about to finally set. During winter construction, the temperature of the ash-sand-polymer mixture entering the mold should not be lower than 5°C, and insulation measures should be taken;

[0042] In some embodiments of the present application, a steel cage is fixed in the mold.

[0043] In some embodiments of the present application, the method for preparing the gray-sand polymer material further comprises brushing a permeable isolation layer on the outer surface of the gray-sand polymer material.

[0044] In some embodiments of the present application, the method for preparing the gray sand polymer material further comprises brushing a potassium methyl silicate permeable isolation layer on the outer surface of the gray sand polymer material.

[0045] According to the third aspect of the present application, the present invention also provides an application of the ash-sand polymer material described in any one of the first aspects or the ash-sand polymer material prepared by any one of the preparation methods described in the second aspect of the present invention in the field of desert building materials or marine engineering materials.

[0046] The present application includes at least one of the following beneficial technical effects:

[0047] In the present application, fly ash, desert sand, slag, and alkali activator work synergistically to carry out geopolymerization reaction, and the strength of the ash-sand polymer material is improved by the coordinated effect of the specific weight ratio of fly ash and desert sand. The raw material components in the present application are simple and low-cost, among which fly ash and slag are solid wastes that need to be harmlessly treated. Therefore, the ash-sand polymer material of the present application can process a large amount of solid waste and realize the resource utilization of waste; and desert sand is a raw material that is easily available in the desert, and the proportion of desert sand used in the present application is relatively large. Therefore, the ash-sand polymer material of the present application is used in desert construction to reduce the cost of desert construction in the desert. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a state diagram of the service life measurement test of the ash-sand polymer material obtained in Example 1 of the present invention;

[0049] Figure 2 The service life measurement test status diagram of C30 cement

[0050] Figure 3 This is a state diagram of the sulfate corrosion resistance test of the gray sand polymer material 10 obtained in Example 2 of the present invention;

[0051] Figure 4 This is the test status diagram of C30's sulfate corrosion resistance performance. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below through specific embodiments, which do not limit the protection scope of the present invention. Some non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the protection scope of the present invention.

[0053] Example 1

[0054] This embodiment provides a novel gray sand ground polymer material, and its formula is as follows:

[0055] Table 1: Example 1 Grey Sand Polymer Material Components

[0056]

[0057] The preparation method of the novel gray sand ground polymer material comprises the following steps:

[0058] (1) Preparing ash sand polymerizer: grinding and activating slag and fly ash. The specific steps of grinding and activating are as follows: grinding with a ball mill at a speed of 800 r / min, 30 min for each of the forward and reverse directions, until the ash sand polymerizer is 800 mesh. After grinding and activating, the specific surface area of ​​the polymerizer is increased and the reaction activity is higher.

[0059] (2) Preparing a gray sand polymerization liquid: dissolving sodium hydroxide in a solvent to form a sodium hydroxide solution, grinding sodium silicate. The specific grinding steps are: grinding using a ball mill at a grinding speed of 500 r / min for a grinding time of 20 min, mixing the ground sodium silicate with the sodium hydroxide solution, and obtaining a gray sand polymerization liquid;

[0060] (3) Preparation of ash-sand polymer material: Mix ash-sand polymerizer and desert sand, then add the mixture of ash-sand polymer liquid and water, stir evenly to obtain ash-sand polymer mixture, pour the ash-sand polymer mixture into a mold, vibrate and compact it, maintain and demould, and obtain ash-sand polymer material; wherein the desert sand used in this step comes from the Taklimakan Desert, with an average particle size of 67.47 μm, an average sphericity of 0.76, an average convexity of 0.94, an average aspect ratio of 0.70, and an average roundness of 0.38; at the same time, during the pouring process, the uniformity, compactness and integrity of the ash-sand polymer mixture should be effectively controlled. The ash-sand polymer mixture is loaded into the mold at one time. When loading, a spatula should be used to insert and tamp along the inner wall of the mold, and the ash-sand polymer mixture should be higher than the upper mouth of the mold. wherein, the mold should be attached or fixed on a vibration table, and the mold should be prevented from jumping freely on the vibration table during vibration. The vibration should continue until the surface slurry comes out and there is no obvious large bubble overflow, and over-vibration is not allowed. When casting a large structure, it should be cast in layers, and the maximum thickness of each layer should not exceed 350mm. The upper layer of concrete should be cast before the lower layer of concrete begins to set. After casting, the casting surface should be smoothed mechanically or manually before the lime-sand-polymer mixture is about to set. During winter construction, the temperature of the lime-sand-polymer mixture entering the mold should not be lower than 5°C, and insulation measures should be taken.

[0061] Through the above preparation method, according to the formula in Table 1, a total of 7 kinds of gray sand polymer materials 1-7 were prepared.

[0062] Effect Example 1

[0063] The compressive strength, flexural strength, service life, antifreeze performance, sand blocking effect and other properties of the ash-sand polymer material 1-7 prepared in Example 1 were compared with those of the C30 concrete, as follows:

[0064] First, the compressive strength test method refers to the concrete compressive strength test rebound method specified in the "Technical Standard for Field Testing of Concrete Structures" GB / T50784-2013, and the rebound hammer is struck horizontally; the flexural strength test method refers to the concrete flexural strength test sampling method in the "Technical Standard for Field Testing of Concrete Structures" GB / T50784-2013, cutting concrete specimens in the punching components, testing the flexural failure load of the specimens, and calculating the flexural strength; the service life performance test method refers to the carbonization test related methods in the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T 50082, measuring the carbonization depth of carbonization in the carbonization box for 7d, 14d, 28d, and 56d; the antifreeze performance test method refers to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T 50082 was carried out by the quick freezing method, and the number of freeze-thaw cycles when the relative dynamic elastic modulus dropped to 80% and 60% was recorded; the detection method of the sand blocking effect performance is: generally, the sand transport rate at different wind speeds is used for characterization, where the sand transport rate refers to: after the sand-carrying airflow is purified by the sand retaining wall, the mass of sand carried by the airflow per unit time on the leeward side, where the calculation formula of the sand transport rate is:

[0065]

[0066] Where: Q is the sediment transport rate [g / (cm 2 ·min)]; M is the collected sand weight (g); Δt is the sand collection time (min); S is the inlet area of ​​the sand collector (cm2).

[0067] According to the above method, the relevant properties of the ash-sand polymer materials 1-7 prepared by Example 1 of the present invention and the C30 concrete were tested, and the results are shown in Table 2-6:

[0068] Table 2 Comparison of compressive strength

[0069] Serial number Experimental samples Compressive strength / MPa 1 Gray sand polymer material 1 71.7 2 Gray sand aggregate material 2 78.22 3 Gray sand aggregate material 3 67.3 4 Gray sand aggregate material 4 63.54 5 Gray sand aggregate material 5 59.45 6 Gray sand polymer material 6 62.71 7 Gray sand aggregate material 7 73.42 8 C30 Concrete 36.67

[0070]

[0071] Serial number Experimental samples Flexural strength / MPa 1 Gray sand polymer material 1 7.83 2 Gray sand aggregate material 2 9.32 3 Gray sand aggregate material 3 6.93 4 Gray sand aggregate material 4 6.65 5 Gray sand polymer material 5 6.34 6 Gray sand polymer material 6 6.61 7 Gray sand aggregate material 7 7.45 8 C30 Concrete 4.7

[0072] Table 4 Service life comparison

[0073]

[0074] The service life comparison charts of ash sand aggregate material 1 and C30 concrete are as follows: Figure 1 , Figure 2As shown in the figure, from left to right, the carbonation depths measured at 7, 14, 28, and 56 days respectively, it can be seen that the service life of the gray sand aggregate material is one order of magnitude higher than that of C30 concrete.

[0075] Table 5 Comparison of antifreeze performance

[0076] Experimental samples N(60) N(80) Gray sand polymer material 1 103 42 Gray sand aggregate material 2 98 39 Gray sand aggregate material 3 97 41 Gray sand aggregate material 4 99 40 Gray sand polymer material 5 97 37 Gray sand polymer material 6 98 40 Gray sand aggregate material 7 96 37 C30 Concrete 73 32

[0077] Among them, N(60) and N(80) represent the number of cycles when the relative dynamic elastic modulus of the specimen drops to 60% and 80%, respectively.

[0078] Table 6 Comparison of sand blocking effect

[0079] Wind speed (m / s) 3 6 10 15 20 25 Gray sand polymer material 1 0 0 0 0.04 0.63 1.32 Gray sand aggregate material 2 0 0 0 0.04 0.63 1.32 Gray sand aggregate material 3 0 0 0 0.04 0.63 1.32 Gray sand aggregate material 4 0 0 0 0.04 0.63 1.32 Gray sand polymer material 5 0 0 0 0.04 0.63 1.32 Gray sand polymer material 6 0 0 0 0.04 0.63 1.32 Gray sand aggregate material 7 0 0 0 0.04 0.63 1.32

[0080] The results presented in Tables 2 to 6 indicate that the ash-sand polymer material prepared by the method provided by the present invention has good mechanical properties and good sand-blocking effect, and can be used for sand prevention; and since the content of desert sand in the raw material of the ash-sand polymer material is relatively high, and desert sand is a raw material that is easily available in the desert, the ash-sand polymer material does not contain any other types of aggregates, fibers and other components, and its composition is relatively simple, easy to make, and has a low production cost; at the same time, the content of fly ash in the raw material of the ash-sand polymer material is relatively high, and fly ash is a solid waste. The method provided by the present invention can effectively treat the waste, and realize the resource utilization of the waste on the basis of reducing the cost of the ash-sand polymer material.

[0081] Comparative Example 1: Investigating the effect of slag on the performance of ash sand aggregate

[0082] This comparative example is based on the components and preparation method of the ash-sand polymer material of the first group of Example 1, and further explores the influence of slag on the performance of the ash-sand polymer material. The difference between this comparative example and the first group of Example 1 is that the slag components in Example 1 are replaced with the following materials in Table 7, and the compressive strength of the prepared ash-sand polymer material is tested. The results are shown in Table 7:

[0083] Table 7 Effect of different components on the strength of ash sand aggregate

[0084]

[0085] The results presented in Table 7 show that compared with materials such as steel slag, furnace slag, iron tailings, red mud, phosphogypsum, and carbide slag, the use of slag in combination with fly ash, alkali activator, and desert sand system can significantly enhance the strength of ash-sand aggregate materials.

[0086] Comparative Example 2: Influence of fly ash on the strength of ash-sand aggregate

[0087] This comparative example is based on the components and preparation method of the ash-sand polymer material of the first group of Example 1, and further explores the influence of fly ash on the performance of the ash-sand polymer material. The difference between this comparative example and the first group of Example 1 is that the fly ash components in Example 1 are replaced with the following materials in Table 8, and the compressive strength of the prepared ash-sand polymer material is tested. The results are shown in Table 8:

[0088] Table 8 Effect of each component on the compressive strength of ash sand aggregate

[0089]

[0090] According to the results presented in Table 8, when the fly ash in the ash-sand polymer material formula provided by the present invention is replaced with steel slag, slag, iron tailings, red mud, phosphogypsum, carbide slag, cement and other materials, the compressive strength of the prepared ash-sand polymer material is significantly reduced. At the same time, it was found in the experimental exploration process that when B4 (red mud) and B6 (carbide slag) were used to prepare the ash-sand polymer material, late cracking was found, and when B3 (slag) was used to prepare the ash-sand polymer material, late expansion was found. It can be seen that in the formula system provided by the present invention, the mutual matching of fly ash with slag, alkali activator and desert sand system can significantly enhance the strength of the ash-sand polymer material.

[0091] Comparative Example 3

[0092] Based on Example 1, this comparative example further explores the effects of the amounts of slag, fly ash, desert sand, alkali activator and other components on the compressive strength performance of the ash-sand polymer material. The results are as follows:

[0093] Table 9 Effect of component dosage on compressive strength of ash sand polymer material

[0094]

[0095] The results shown in Table 9 indicate that the absence of any one of the components of slag, fly ash, desert sand and alkali activator will significantly affect the compressive strength performance of the ash-sand polymer material. At the same time, the present invention has found in the research that C3 cannot gel due to the absence of alkali activator, and C4 and C5 have the problem of late cracking.

[0096] Comparative Example 4

[0097] Based on Example 1, this comparative example further explores the effect of the ratio of desert sand to fly ash on the compressive strength of the ash-sand polymer material. The difference between this comparative example and Example 1 is that the ratio of desert sand to fly ash is different. The results are shown in Table 10:

[0098] Table 10 Effect of different ratios of desert sand and fly ash on the compressive strength of fly ash-sand aggregates

[0099]

[0100]

[0101] The results presented in Table 10 indicate that the ratio of desert sand to fly ash significantly affects the compressive strength of the fly ash-sand aggregate.

[0102] Comparative Example 5

[0103] Machine-made sand is made of rocks, pebbles, mine waste rocks and tailings, etc., and is processed by mechanical crushing, shaping, screening, powder control and other processes after soil removal. The gradation, particle size and stone powder content meet the requirements and the particle size is less than 4.75 mm. Most of the solutions for treating desert sand disclosed in the prior art use machine-made sand. Based on this, this comparative example is based on Example 1, and the influence of machine-made sand on the gray sand polymer material of the present invention is explored. The results are shown in Table 11:

[0104] Table 11 Effect of machine-made sand on compressive strength of ash-sand aggregate

[0105]

[0106] The results presented in Table 11 indicate that in the formulation system provided by the present invention, the effect of using the machine-made sand disclosed in the prior art to replace desert sand in preparing the gray sand polymer material is not as good as that of desert sand.

[0107] Comparative Example 6

[0108] Since cement and alkali activator will produce a coagulation reaction, the mixing process will cause the plastic to become hard and unable to be formed, so the strength cannot be tested. Therefore, the experimental group in this comparative example only gelled the raw materials with cement.

[0109] Table 12 Effect of different cementitious raw materials on the strength of ash sand aggregate

[0110] The experimental results show that when cement is used as the cementitious material, its effect is not as good as that of using an alkali activator. The origin Comparative Example 7

[0111] Based on Example 1, this comparative example further explores the effect of the ratio of sodium silicate to sodium hydroxide in the alkali activator on the compressive strength of the gray sand polymer material. The difference between this comparative example and Example 1 is that the ratio of sodium silicate to sodium hydroxide is different. The results are shown in Table 13:

[0112] Table 13 Effect of different ratios of sodium silicate and sodium hydroxide on the compressive strength of ash sand polymer materials

[0113]

[0114] The results presented in Table 9 indicate that the ratio of sodium silicate to sodium hydroxide significantly affects the compressive strength of the ash sand aggregate.

[0115] Example 2

[0116] A gray sand polymer material, the formula of which is as follows:

[0117] Table 14 Raw materials and dosage

[0118] The preparation method of the gray sand polymer material comprises the following steps:

[0119] (1) Preparation of ash sand polymerizer: grinding and activating slag and fly ash. The specific steps of grinding and activation are as follows: grinding with a ball mill at a speed of 800 r / min, 30 min for each of the forward and reverse directions, to 800 mesh (please add), and obtaining an ash sand polymerizer. After grinding and activation, the polymerizer has a larger specific surface area and a higher reaction activity;

[0120] (2) Preparing the ash sand polymerization liquid: After grinding the alkaline activator, the specific grinding steps are: grinding using a ball mill, grinding speed 500r / min, grinding time 20min, adding solvent water and mixing, to obtain the ash sand polymerization liquid;

[0121] (3) Preparation of ash-sand polymer material: Mix ash-sand polymerizer and marine sand, then add a mixture of ash-sand polymer liquid and water, stir evenly to obtain ash-sand polymer mixture, pour the ash-sand polymer mixture into a mold, vibrate and compact it, maintain and demould, and obtain ash-sand polymer material; wherein, the marine sand used in this step comes from the ocean beach, and is sieved and treated to remove impurities, and the fineness modulus is 2.1 to 2.6; at the same time, during the pouring process, the uniformity, density and integrity of the ash-sand polymer mixture should be effectively controlled. The ash-sand polymer mixture is loaded into the mold at one time. When loading, a spatula should be used to tamp along the inner wall of the mold, and the ash-sand polymer mixture should be higher than the upper mouth of the mold. The mold should be attached or fixed on a vibration table. During vibration, the mold should be prevented from jumping freely on the vibration table. The vibration should continue until the slurry comes out of the surface and there are no obvious large bubbles overflowing. Over-vibration is not allowed. When casting a large structure, it should be cast in layers, and the maximum thickness of each layer should not exceed 350mm. The upper layer of concrete should be cast before the lower layer of concrete begins to set. After casting, the casting surface should be smoothed mechanically or manually before the lime-sand-polymer mixture is about to set. During winter construction, the temperature of the lime-sand-polymer mixture entering the mold should not be lower than 5°C, and insulation measures should be taken.

[0122] By the above preparation method and according to the formula in Table 14, the ash sand polymer material 10 is prepared.

[0123] Effect Example 2

[0124] The compressive strength, flexural strength, sulfate corrosion resistance, and chloride ion penetration resistance of the ash-sand polymer material 10 prepared in Example 2 were compared with those of C30 concrete, as shown in the following:

[0125] First, the compressive strength and flexural strength testing methods are as follows: refer to the national standard "Technical Standard for Field Testing of Concrete Structures" GB / T50784-2013); the sulfate erosion resistance testing method is to refer to the national standard "Standard for Experimental Methods of Long-term Performance and Durability of Ordinary Concrete" GB / T50082-2009 for sulfate resistance testing, and use the dry-wet cycle test method to determine the sulfate erosion resistance of the ash sand polymer material and C30 concrete; the chloride ion penetration resistance testing method is as follows: refer to the national standard "Standard for Experimental Methods of Long-term Performance and Durability of Ordinary Concrete" GB / T50082-2009 for chloride ion penetration testing, and use the electric flux test method to determine the chloride ion penetration resistance of the ash sand polymer material 2 and C30 concrete. The relationship between electric flux and chloride ion permeability is shown in Table 15:

[0126] Table 15 Relationship between electric flux and chloride ion permeability

[0127] Charge passed (Coulombs) Chloride ion permeability >4000 High 2000-4000 Moderate 1000-2000 LowLow 100-1000 VeryLow <100 Negligible

[0128] According to the above method, the relevant properties of the ash-sand polymer material 10 prepared by Example 2 of the present invention and the C30 concrete were tested, and the results are shown in Tables 16-18:

[0129] Table 16 Comparison of compressive strength performance

[0130]

[0131]

[0132] Table 17 Comparison of sulfate corrosion resistance

[0133]

[0134] Table 18 Comparison of resistance to chloride ion penetration

[0135] Serial number Experimental samples Electric flux 1 Gray sand polymer material 10 173.47C 2 C30 Concrete 1683.2C

[0136] The results presented in Tables 15-17 above show that the ash sand polymer material 10 prepared by the method provided in Example 2 has good mechanical properties, good resistance to sulfate erosion and resistance to chloride ion penetration, and can be used in marine engineering materials. And because the raw material of the ash sand polymer material has a high content of marine sand, which is a readily available raw material in the marine and island environments, the ash sand polymer material does not add other types of aggregates, fibers and other components, and its composition is relatively simple and easy to make. Therefore, the production cost of the ash sand polymer material is low. At the same time, the raw material of the ash sand polymer material has a high content of fly ash, which is a solid waste. Therefore, the polymer can effectively treat waste and realize the resource utilization of waste on the basis of reducing the cost of the polymer.

[0137] Example 3

[0138] This embodiment provides a gray sand polymer material based on Embodiment 1, and its formula is shown in Table 19 below. The difference between this embodiment and Embodiment 1 is that the preparation method is not exactly the same. In the preparation method of this embodiment, in the step (3) of preparing the gray sand polymer material, it also includes fixing a steel cage in a fixed mold, wherein the diameter of the steel bars in the steel cage is 6 mm.

[0139] The method for making the steel cage refers to the "Code for Construction of Building Foundation Engineering" GB 51004-2015; the prepared steel cage is fixed in the mold by placing pads to ensure the thickness of the protective layer.

[0140] Table 19 Raw materials and dosage

[0141]

[0142] By the above preparation method and according to the formula in Table 19, the ash sand polymer material 11 was prepared.

[0143] Example 4

[0144] This embodiment provides a gray sand polymer material based on Embodiment 1, and its formula is shown in Table 19 above. The difference between this embodiment and Embodiment 1 is that the preparation method is not exactly the same. In the preparation method of this embodiment, in the step (3) of preparing the gray sand polymer material, it also includes fixing a steel cage in a fixed mold. The manufacturing method, size, arrangement and fixation of the steel cage are the same as those in Embodiment 3, wherein the diameter of the steel bars in the steel cage is 10 mm.

[0145] By the above preparation method, according to the formula in Table 19, a gray sand polymer material 12 was prepared.

[0146] The compressive strength performance of the two gray sand polymer materials prepared in Example 3 and Example 4 was tested, and the results are shown in Table 20:

[0147] Table 20 Compressive strength properties of ash sand aggregate material after adding steel cage

[0148] Serial number Experimental samples Compressive strength / MPa Flexural strength / MPa 1 Gray sand aggregate material 11 73.76 8.71 2 Gray sand aggregate material 12 75.88 10.03

[0149] The results shown in Table 18 indicate that fixing the steel cage in a fixed mold can significantly enhance the compressive strength and flexural strength of the prepared gray sand aggregate material.

[0150] Example 5

[0151] This embodiment provides a gray sand polymer material based on Example 1, and its formula is shown in Table 19 above. The specific preparation method is not completely different. In this embodiment, in step (3) of the preparation method of Example 1, it also includes brushing a potassium methyl silicate isolation coating on the surface of the gray sand polymer material after the curing age reaches 7 days. Through the above preparation method, according to the formula in Table 19, a gray sand polymer material 13 is prepared, and the antifreeze performance test is carried out using the detection method of Effect Example 2. The results are shown in Table 21:

[0152] Table 21 Effect of coating on antifreeze performance

[0153] Serial number Gray sand aggregate material 13 Measurement results / (times) Measurement Item 1 N(60) 169 Measurement Item 2 N(80) 46

[0154] The results shown in Table 21 indicate that applying a potassium methyl silicate isolation coating on the surface of the gray sand polymer material can enhance the antifreeze performance of the gray sand polymer material.

[0155] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.

Claims

1. A gray sand polymer material, characterized in that: The ash-sand polymer material comprises the following raw materials in parts by weight: 100-400 parts of fly ash, 100-1000 parts of desert sand / ocean sand, 50-300 parts of slag; 30-220 parts of alkali activator, 25-200 parts of solvent; wherein the weight ratio of the fly ash to the desert sand is 0.2-1.

4.

2. The ash sand polymer material according to claim 1, characterized in that: The ratio of fly ash to desert sand is 0.46-0.9; preferably, the ratio of fly ash to desert sand is 0.

7.

3. The ash sand polymer material according to claim 1, characterized in that: The solvent includes one or more of pure water, tap water, brackish water, seawater, and waste alkali solution.

4. The ash sand polymer material according to claim 1, characterized in that: The alkaline activator is selected from two or more of sodium silicate, sodium hydroxide, potassium hydroxide and calcium hydroxide; Preferably, the alkaline activator comprises 25-170 parts of sodium silicate and 5-50 parts of sodium hydroxide; Preferably, the alkaline activator comprises 30-150 parts of sodium silicate and 10-35 parts of sodium hydroxide.

5. The ash sand polymer material according to claim 1, characterized in that: The particle size of the desert sand is 100-400 mesh aeolian sand, and the particle size distribution of the desert sand is between 0.074 and 0.250 mm; Preferably, the fly ash is selected from one or more of primary, secondary and tertiary fly ash; Preferably, the fly ash contains 3-5% calcium oxide, 49-51% silicon oxide, 26-28% aluminum oxide, and 6-8% iron oxide; preferably, the fly ash is selected from primary fly ash, which is air-selected primary fly ash produced by coal-fired power generation units of 600 megawatts or more and which is not ground and conforms to GB / T 1596.

6. A method for preparing the gray sand polymer material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparing a ash-sand polymerizer: grinding and activating slag and fly ash to obtain a ash-sand polymerizer; (2) preparing a ash sand polymerization liquid: grinding an alkali activator, adding a solvent and mixing well to obtain an ash sand polymerization liquid; (3) Preparation of ash-sand polymer material: Mix ash-sand polymerizer with desert sand and / or ocean sand, then add ash-sand polymer liquid and solvent, stir evenly, pour into a mold, vibrate and compact, cure and demould, and obtain ash-sand polymer material.

7. The method for preparing the gray sand polymer material according to claim 6, characterized in that: In step (1), the grinding activation conditions include: grinding speed of 700-900 r / min, forward and reverse grinding for 20-40 min each, to 700-900 mesh; Preferably, in step (2), the conditions of the alkali-induced grinding include: a grinding speed of 400-600 r / min and a grinding time of 10-30 min; Preferably, in step (2), the amount of the solvent used is 22-100 parts by weight; Preferably, in step (2), the amount of the solvent used is 30-70 parts by weight; Preferably, in step (3), the amount of the solvent used is 3-100 parts by weight; Preferably, in step (3), the amount of the solvent used is 3-50 parts by weight.

8. The method for preparing gray sand polymer material according to claim 6, characterized in that: A steel cage is fixed in the mold.

9. The method for preparing gray sand polymer material according to claim 6, characterized in that: The method comprises brushing a permeable insulating layer on the outer surface of the gray-sand polymer material; preferably, the method comprises brushing a permeable insulating layer of potassium methyl silicate on the outer surface of the gray-sand polymer material.

10. Use of the ash-sand polymer material as claimed in any one of claims 1 to 5 or the ash-sand polymer material prepared by the preparation method as claimed in any one of claims 6 to 9 in the field of desert building materials or marine engineering materials.

Citation Information

Cited By

  • High-strength lime-sand polymerized building material and preparation method thereof

    CN120423829A